PERSEPSI GURU DAN RESPON PESERTA DIDIK TERHADAP MATA PELAJARAN IPS DI KABUPATEN SUMBAWA - suharli, suharli - (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Perception of Teachers and Student Responses to Social Studies Education Subjects. This study aims to explore the teacher’s perception and students' responses to social studies education subject at junior high school in Sumbawa Regency-NTB. This research uses quantitative descriptive approach with survey research type. Data collection in this study using a questionnaire. 27 junior high schools in three zones of Sumbawa Regency-NTB are 9 junior high schools representing schools in western Sumbawa, 9 junior high schools representing schools in central Sumbawa, and 9 junior high schools representing schools in eastern Sumbawa as samples. Research subjects were 27 teachers of social studies education and 450 students in grade VIII junior high schools of Sumbawa Regency. The results showed, most teachers (74.07%) said that the subjects of social studies education are very easy to teach because the material is directly related to the real conditions in society. While most of the students also had a positive outlook, 82% of the students said that social studies education materials is very easy to understand, 61% of the students said that the social studies education materials were largely shaped memorization, 34% of the students said that the social studies education material was too broad so difficult to master, 90% of students said that the social studies education material is very useful, 93% of students stated very interested in studying social studies education and 74% of students said always taking the time to study the material of social studies.Keywords: Teacher's Perception, Student Responses, and Social Studies Education Subject